2019
DOI: 10.26434/chemrxiv.10257686.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnesium-Accelerated Maillard Reactions Drive Differences in Adjunct and All-Malt Brewing

Abstract: Magnesium impacts key processes in brewing including yeast metabolism and mash pH but is typically overshadowed in brewing studies, owing to the established centrality of calcium. Using flame atomic absorption spectroscopy (FAAS), we have identified a 33.7% average increase in magnesium concentration in commercially available beers brewed with 100% barley malt versus those brewed with adjunct grains. Parallel analysis of brewing grains implicates rice in driving this discrepancy. Given the known catalytic prop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The catalytic properties of magnesium during Maillard reaction are well known ( Rizzi, 2008 , 2010 ; O'Brien, 1997 ). Omari el al. (2019) showed that the catalytic effect of magnesium in beer color development is significant, persisting for about 20 min.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic properties of magnesium during Maillard reaction are well known ( Rizzi, 2008 , 2010 ; O'Brien, 1997 ). Omari el al. (2019) showed that the catalytic effect of magnesium in beer color development is significant, persisting for about 20 min.…”
Section: Resultsmentioning
confidence: 99%